2021
DOI: 10.1021/acs.jmedchem.1c00354
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Benzimidazole Derivatives Incorporating Phenolic Mannich Base Side Chains Inhibit Microtubule and Hemozoin Formation: Structure–Activity Relationship and In Vivo Oral Efficacy Studies

Abstract: A novel series of antimalarial benzimidazole derivatives incorporating phenolic Mannich base side chains at the C2 position, which possess dual asexual blood and sexual stage activities, is presented. Structure–activity relationship studies revealed that the 1-benzylbenzimidazole analogues possessed submicromolar asexual blood and sexual stage activities in contrast to the 1H-benzimidazole analogues, which were only active against asexual blood stage (ABS) parasites. Further, the former demonstrated microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These are able to treat a broad range of disorders, particularly epilepsy, diabetes, and pregnancy. Such derivatives exhibit a variety of bioactivities like antiallergic [ 61 ], antihistamine [ 62 ], anti-ulcerative, antiproliferative [ 63 ], antioxidant [ 64 , 65 ], antifungal, antibacterial, antitubercular [ 66 ], antihypertensive [ 67 ], anti-inflammatory, analgesic, antiamoebic [ 68 ], antitumor [ 69 , 70 , 71 ], antimalarial [ 72 ], and anti-kinase activity [ 73 ]. Several BnZ derivatives are also being investigated as cholinesterase inhibitors and anti-parasitic drugs [ 74 , 75 , 76 , 77 ].…”
Section: Multifaceted Efficacy Of Benzimidazolementioning
confidence: 99%
“…These are able to treat a broad range of disorders, particularly epilepsy, diabetes, and pregnancy. Such derivatives exhibit a variety of bioactivities like antiallergic [ 61 ], antihistamine [ 62 ], anti-ulcerative, antiproliferative [ 63 ], antioxidant [ 64 , 65 ], antifungal, antibacterial, antitubercular [ 66 ], antihypertensive [ 67 ], anti-inflammatory, analgesic, antiamoebic [ 68 ], antitumor [ 69 , 70 , 71 ], antimalarial [ 72 ], and anti-kinase activity [ 73 ]. Several BnZ derivatives are also being investigated as cholinesterase inhibitors and anti-parasitic drugs [ 74 , 75 , 76 , 77 ].…”
Section: Multifaceted Efficacy Of Benzimidazolementioning
confidence: 99%
“…However, haem detoxification is not critical for gametocyte development, suggesting an alternative MOA for their transmission-blocking activity (van Biljon et al, 2019). Another series of benzimidazole derivatives that were structurally related to PBI.109 and PBI.105 were found to inhibit microtubule formation in P. falciparum (Dziwornu et al, 2021). In P. falciparum, microtubules are crucial for cell division during asexual blood stage and critical for maintaining the inner membrane functionality for gametocyte development (Gerald et al, 2011;Parkyn Schneider et al, 2017).…”
Section: Inhibiting the Haem Detoxification Processmentioning
confidence: 99%
“…On exploring further about benzimidazole mannich base analogues it was found that antimalarial activity of some compounds bearing side chain of mannich base having phenolic group having benzimidazole nucleus (15) that inhibit mitotic spindle formation were synthesized and evaluated by Chibale et al, and their in vivo investigation in Plasmodium Berghei exposed that some compounds exhibited high efficacy when oral administration of these scaffolds was done (23).…”
Section: Anti-plasmodium Activitymentioning
confidence: 99%